Right atrial and ventricular echocardiographic strain analysis predicts requirement for right ventricular support after left ventricular assist device implantation. (13th April 2018) - Charisopoulou, Dafni; Banner, Nicholas R; Demetrescu, Camil; Simon, Andre R; Rahman Haley, Shelley
Abstract: Aims: The need for right ventricular assist device (RVAD) support after left ventricular assist device (LVAD) therapy is associated with increased morbidity and mortality. We used 2D echocardiographic strain analysis to assess right atrial (RA) and right ventricular (RV) mechanics and predict the need for RV mechanical support after LVAD implantation. Methods and results: Seventy advanced chronic heart failure (ACHF) patients [59 male, age 47 ± 12 years, 79% dilated cardiomyopathy, left ventricular ejection fraction 23 ± 10%] received continuous-flow LVAD as a bridge to transplantation over an 18 month period. A retrospective analysis of RV and RA strain and right heart dyssynchrony was performed comparing those requiring RVAD (20%, n = 14) with those who did not (non-RVAD 80%, n = 56). One-year survival was significantly lower in the RVAD group (50% vs. 79%; P < 0.03). Independent predictors of RVAD support were: low peak RA longitudinal strain (RALS) [odds ratio (OR) 2.5, 95% confidence interval (95% CI) 1.37–2.0; P = 0.03], low RV free-wall longitudinal strain (RVFWLS) (OR 1.3, 95% CI 1.03–2.3; P = 0.04), and degree of intra-RV dyssynchrony (DRVFW-IVS, OR 1.3, 95% CI 1.02–1.3; P = 0.04). Conclusion: In LVAD recipients needing RVAD support, there was lower RALS and RVFWLS in addition to greater RV free-wall mechanical delay. We conclude that RA and RV strain and dyssynchrony analysis have the potential to add incremental value to the pre-VAD-implantation assessment made using conventional echo measurements.